Analisis Kalimat Tidak Efektif pada Buku Panduan Capaian Pembelajaran Elemen Jati Diri untuk Pengajar PAUD - Safinda Fitriana; Novi Amelia Oktaviani; Avita Setiawati; Dita Luluk Safitri; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Ineffective sentences are sentences that use several words that are difficult to understand. This research is motivated by the authors in the arrangement of sentences in books that are not in accordance with linguistic rules. This analysis aims to determine effective and ineffective sentences. This study aims to make teacher candidates know the ineffective sentences used in teaching. The method used in this method focuses on systematic and procedural. The method used is a methodological approach in the form of a descriptive approach and a theoretical approach in the form of a syntactic approach. This study uses qualitative description data by applying reading, observing, and note-taking techniques. In analyzing the data using literature study techniques sourced from scientific journals. While the technique of presenting data using tables. Secondary data sources are used in this study. This data source uses two sources, namely written and photos. In this study document data and laptops are needed. This study produced several ineffective sentences which were classified into 4, namely wastage of words, there were 12 sentences. Inaccurate use of conjunctions in 8 sentences, inaccurate use of words in 10 sentences, and inaccuracy in punctuation in 10 sentences. This study is useful as a guide in writing effective sentences, besides that the writer can pay more attention to writing in the preparation of the book.